Foliar fertilization for the growth and yield of Capsicum chinense Jacq. under screenhouse conditions (Agroindustrial Science, 2025)
The cultivation of habanero chili (Capsicum chinense Jacq.) has gained interest in the central Pacific of Mexico. The objective was to evaluate foliar fertilizers on the growth and yield of habanero pepper under screenhouse conditions. Three foliar fertilizers were evaluated: T1) Fruto grande® + 4-4-50®, T2) Fruto grande®, T3) 4-4-50®, T4) Poliquel multi® and a control T5) without foliar fertilizer. The response variables were plant height, stem diameter, leaf area, chlorophyll index, fruit quality (weight, length and width) and yield (fruits plant-1, kg plant-1 and t ha-1). A randomized design was used, and data were analyzed with analysis of variance and Tukey comparison of means (p = 0.05). Plant height, stem diameter and leaf area did not show significant differences due to the effect of foliar fertilizers. The three foliar fertilizers increased the chlorophyll index by 4.42% to 17.19%. The combination of Fruto grande® + 4-4-50® increased fruit size in weight (2.89 g), length (4.32 mm), and width (2.67 mm). However, foliar fertilizers did not increase yield, which ranged from 0.95 to 1.14 kg plant-1. Foliar fertilizers increase fruit size but not yield.
Keywords: Colima; chlorophyll; habanero; vegetable; micronutrients